A rare case of air cysto-uretero-pyelogram due to emphysematous cystitis - Shakti Swarup Sarangi; Deepak Prakash Bhirud; Shiv Charan Navriya; Arjun Singh Sandhu (Indian Journal of Urology, 2023)
Emphysematous infection of the urinary tract is a hazardous condition and is life-threatening if not managed quickly. We report an 82-year-old woman with uncontrolled diabetes mellitus and urethral stricture who presented with emphysematous cystitis with the gas reaching up to the pelvicalyceal system on the left side (emphysematous pyelonephritis) and appearing in X-ray as air pyelogram. The patient was managed with drainage and intravenous antibiotics and she recovered.